Simulations of photon versus particle therapy for treating cancer in canines using matrad: case study of a beagle with pituitary macroadenoma - Ristova, Mimoza; Gjoreska, Andrijana; Simonovska, Marija; Lukarski, Dushko; Celeska, Irena (Faculty of Veterinary Medicine, University of Belgrade, Serbia, 2025)
In this study, we propose that dogs diagnosed with tumors exhibiting a similar pathology to those in humans could play a crucial role in trials for novel radiation therapy modalities, such as particle therapy (beyond protons and carbon ions) or FLASH therapy. A multidisciplinary team including a veterinary oncology scientist, a human radiation oncologist, and medical physicists, conducted a simulation of a comparative treatment planning using matRad software to compare the benefits of three treatment modalities: (1) X-rays, (2) protons, and (3) carbon ions. Diagnostic results from a Beagle dog with a pituitary macroadenoma were utilized for this study. The dog was euthanized due to severe deterioration in basic physiological functions, including eating, swallowing, breathing, head tilt, and movement, over a period of several days. The dog’s owner, who is closely related to one of the coauthors, provided oral consent for the use of all available clinical data from the deceased dog. These results were used as a hypothetical case to simulate and compare the effectiveness of three radiation treatment modalities. This pioneering approach opens an avenue to the potential of involving living companion animals already diagnosed with cancer in treatment research, advancing both veterinary and human oncology. The results suggested that if treated with radiation, the dog would have benefited most from particle therapy, which delivers a maximum dose to the tumor while considerably minimizing exposure of the surrounding critical organs – an advantage not achieved with conventional X-rays. This collaboration emphasizes the importance of integrating veterinary and human radiation oncology. This work paves the way for developing initial protocols to treat pets with cancer, serving as a preclinical foundation before clinical studies are conducted on humans.
Keywords: Macroadenoma in canine; matRad; particle therapy; protons and C-ions; translation from veterinary to clinical trial